Review The Design of “Kampung Tematik Malang 2016” on Kampung Kramat Kasin, Malang, Indonesia - Josaf Sayoko; Erna Winansih; Junianto Junianto (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Sustainable development is the main city building and become. Along with the city will increase settlement slums and settlement wild/squatter (Kustianingrum, 2010 ). Efforts to do the government as policy management governance to control the growth that it can unrestrained, lead to the state of the environment, social and economic bad. One government efforts by means of the bottom up involving public participation in developing the quality of their packed become a “Festival Rancang Malang” with 57 competition in the Kelurahan within Malang city is expected to their thematic born typical Malang city. Their which was growing in sprawls, kind of unplanned and tend to slums can set and designed of an idea residents of accompanied by Academics College and professional associations architect especially. And therefore the design physical and non-physic produced is expected to provide solutions problem solving in terms of there so as to be a region that identity and benefit the citizens of its inhabitants, and to maintain ecological sustainability. In a review this design writer trying to dissect design their Kampung Kramat Kasin as one competition winner devise Festival Rancang Malang 2016. The findings review was able to deliver in its design comprehensive.